West African Economic and Monetary Union (WAEMU) : Recent Economic Developments and Regional Policy Issues; and Public Information Notice on the Executive Board Discussion. (IMF Staff Country Reports; Country Report ;, 2003)
This report examines recent economic developments and regional policy issues in the West African Economic and Monetary Union (WAEMU). Although progress has been achieved on the integration front since 1994, including the establishment of a customs union and the creation of the economic union, the momentum of integration appears to have slowed in recent years. Progress toward convergence of the WAEMU countries during 2001 and 2002 was below expectations, and difficulties were encountered in the effective implementation of various regional reforms.